Cybersecurity in Israel - Tabansky, Lior.; Ben Israel, Isaac; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This SpringerBrief gives the reader a detailed account of how cybersecurity in Israel has evolved over the past two decades. The formation of the regions cybersecurity strategy is explored and an in-depth analysis of key developments in cybersecurity policy is provided. The authors examine cybersecurity from an integrative national perspective and see it as a set of policies and actions with two interconnected goals: to mitigate security risks and increase resilience and leverage opportunities enabled by cyber-space. Chapters include an insight into the planning and implementation of the National Security Concept strategy which facilitated the Critical Infrastructure Protection (CIP) agreement in 2002, (one of the first of its kind), the foundation of the Israeli Cyber-strategy in 2011, and details of the current steps being taken to establish a National Cyber Security Authority (NCSA). Cybersecurity in Israel will be essential reading for anybody interested in cyber-security policy, including students, researchers, analysts and policy makers alike.
Foreword -- List of Abbreviations -- Introduction -- Geopolitics and Israeli Strategy -- The National Innovation Ecosystem of Israel -- Mid 1990$1 (Bs: The Prequel for National Cybersecurity Policy -- The Israeli National Cybersecurity Policy Focuses on Critical Infrastructure Protection (CIP) -- Seeking Cyberpower: The National Cyber Initiative, 2010 -- The National Cyber-Strategy of Israel and the INCB -- Towards Comprehensive National Cybersecurity -- Striking with Bits? The IDF and Cyber-Warfare -- Conclusion.s
Keywords: Computer science; Political science; Computer security; Computers; Law and legislation; Economic policy; Computer Science; Legal Aspects of Computing; Political Science; R & D/Technology Policy; Systems and Data Security; Electronic books